Effects of short-term sediment nutrient enrichment and grazer (Neritina reclivata) removal on sediment microalgae in a shallow eutrophic estuary (Alabama, USA) - Cebrian, Just (2012)
The olive snail (Neritina reclivata) is ubiquitous in tropical and sub-tropical systems of the Gulf of Mexico, however its impacts on sediment microalgae have been little studied. Many coastal systems around the world are being eutrophied due to human activities, and seemingly they will continue to be eutrophied to a further extent in the future. Exploring the single and combined impacts of further nutrient enrichment and grazing by the olive snail on sediment microalgae in such eutrophic systems is an important question for our understanding and management of these systems. Here we examine the effects of short-term nutrient enrichment and grazing by the olive snail N. reclivata on sediment microalgal biomass and composition in a shallow eutrophic estuary (Weeks Bay, Alabama, USA) of the Northern Gulf of Mexico. For this, we performed a series of factorial experiments adding or not nutrients and removing or not the snail, for a total of four treatments in each experiment: ambient grazing, ambient nutrients; ambient grazing, increased nutrients; no grazing, ambient nutrients; and no grazing, increased nutrients. We did not find any significant impact of nutrient addition in any of the eight short-term (i.e. four days) experiments carried out. Impacts by the snail were minor; we only found a decrease in biomass due to snail grazing in one of the eight experiments, and no impacts on microalgal (i.e. diatom) composition. High ambient nutrient concentrations in the sediment porewater and low snail abundances on the sediment could explain these findings. Our results suggest that ephemeral, short-term nutrient pulses into eutrophic coastal systems of the Northern Gulf of Mexico, such as Weeks Bay (Alabama, USA), should not greatly affect the abundance of sediment microalgae, even though those pulses occur in well-lit areas. The results further suggest the snail N. reclivata is not a major control of sediment microalgal populations in the subtidal sedimentary areas studied. Our findings contrast with the results of past work in sediments with well-lit and nutrient poor conditions, or sediments with high densities of other snail grazers. In conjunction this and other investigations indicate that the response of sediment microalgae to nutrient enrichment and modified grazer abundance depends to a large extent on the initial levels of nutrient availability and grazing before the system is altered.